2013
DOI: 10.2522/ptj.20120412
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Therapeutic Exercise on Pain and Disability in the Management of Chronic Nonspecific Neck Pain: Systematic Review and Meta-Analysis of Randomized Trials

Abstract: Background Given the prevalence of chronic nonspecific neck pain (CNSNP) internationally, attention has increasingly been paid in recent years to evaluating the efficacy of therapeutic exercise (TE) in the management of this condition. Purpose The purpose of this study was to conduct a current review of randomized controlled trials concerning the effect of TE on pain and disability among people with CNSNP, perform a meta-anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
125
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(137 citation statements)
references
References 32 publications
11
125
0
1
Order By: Relevance
“…30,40 Various types of therapeutic exercise have been found to be effective for patients with nonspecific neck pain 2,30 but have been studied only sparsely for patients with cervical radiculopathy. Cervical traction is another frequently recommended, yet inadequately researched, treatment for patients with cervical radiculopathy.…”
Section: T T Conclusionmentioning
confidence: 99%
“…30,40 Various types of therapeutic exercise have been found to be effective for patients with nonspecific neck pain 2,30 but have been studied only sparsely for patients with cervical radiculopathy. Cervical traction is another frequently recommended, yet inadequately researched, treatment for patients with cervical radiculopathy.…”
Section: T T Conclusionmentioning
confidence: 99%
“…Another systematic review evaluating the effects of exercises in office workers with neck pain (with no definite exclusion criteria for discogenic neck pain) advocated muscle strengthening or muscle endurance exercises (20). The most recent systematic review confirmed the short-and intermediate-term pain-relieving effects of therapeutic exercise in patients with nonspecific chronic neck pain in general (21). A recent exercise trial for neck pain patients, including those with pain radiating to the upper extremity, yielded similar results in terms of pain relief in the short term and global perceived effect, with supervised neck and upper body strengthening exercise (the intensity of which was individualized to the specific patient) with and without cervical and thoracic spine manipulation using high-velocity, low-amplitude thrust techniques (22).…”
Section: Exercisementioning
confidence: 99%
“…The PA&E in this trial were based and modified from previous studies [193,216] which reported improvements in pain intensity and strength for women with pain in the neck-and shoulder muscles. PA&E in various combinations are often used for the treatment of chronic pain [3,[33][34][35][36][37][38][39]. However, despite the large amount of research on PA&E as treatment for chronic pain, there is still a lack of knowledge on physiological effects mechanisms behind the positive effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, in accordance with the suggestion that chronification of pain might be related to an imbalance between facilitating and inhibitory neurobiological systems [47,236], it is important to highlight the potential of PA&E to impact both ascending pain inducing activities as well as pain modulatory and descending activities in the nervous system. In future studies, the clinical effect on pain intensity and function as a result of different types of PA&E might not be of main interest to evaluate further, as several reviews [3,33,34,[36][37][38][39] and a metaanalyse [35] consistently shows that PA&E of different types are beneficial for chronic pain. To advance the research field, it might instead be interesting to add a focus on the physiological and neurobiological effect mechanisms associated to acute and long-term effects of PA&E in chronic pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation